(untitled) (Medico Legal Update, 2021)
Background: Shift report has crucial on achieving effective, safe, and high quality communication when the responsibility for the patient care is transferred from one nurse to another in suitable manner. Aim of Study: The study aimed to develop quality of reporting among nurses after implementation of shift report training program. Subjects and Method: The study was conducted at Shoubra General Hospital which affiliated ministry of health hospitals Total bed capacity is (200) bed. Two groups of subjects participated in the study, namely head nurses, staff nurses; 50 head nurses and their assistants in the designated setting, the only selection criterion for this group was working in the selected units during the time of the study; and 129 staff nurses out from 194 according this equation. Three data collection tools were used to carry out this study namely, knowledge questionnaire sheet, Observational check list, Audit sheet. The study involved assessment, planning, implementation, and evaluation phases at the end of training and three months follow-up. Results: No one of the staff nurses in the study sample had satisfactory total knowledge scores at the preintervention phase and reach 100% at the post-intervention and follow up phases. No one of the head nurses in the study sample had satisfactory total performance scores at the pre-intervention phase and reach 100% at the post- intervention phase, while the follow-up phase showed some declines, down to 70% in total performance scores. Conclusion and Recommendations: There was a statistically significant correlation between head nurses’ total knowledge, performance, and audit scores with p-value > 0.01, also, there was a statistically significant correlation between nurses’ total knowledge, performance, and audit scores with p-value > 0.01. The study recommends Periodic assessment of head nurses and their staff for reporting skills. Regular implementation of training programs regarding shift report.